Graphene and Its Derivatives for Electrochemical Sensing - Haoliang Ren (Sensors)
As a typical two-dimensional material, graphene and its derivatives exhibit many excellent properties, such as large specific surface area, electrical properties, and stability. Along with its derivatives, particularly graphene oxide (GO) and reduced graphene oxide (rGO), graphene materials have been studied in various fields due to the presence of aromatic ring, free π-π electron and reactive functional groups. This review focuses firstly on the synthesis methods of graphene and its derivatives along with their properties, followed by a discussion of the applications of their served as functional units in electrochemical sensing. Finally, this review describes the challenges, strategies, and outlooks on future developments.